Medicinal Plants Scenario in Darjeeling Himalayas : Conservation and Cultivation as Alternative Crop - Chhetri, D. R. (Indian Forester, 2007)
The traditional agricultural practice in Darjeeling Himalayan region is characterized by low input, low risk and low yield. Lack of irrigation, small land holdings, difficult terrain and nutrition depletion etc., limit the area of operation for agriculture. Therefore, for the farmers here, a high economic return from limited land holding, maintenance of sustainable conditions and preservation of biodiversity are the challenges. Considering the special conditions in Darjeeling Himalayas, the best way of sustenance is to go for high-value, low-volume cash crops. Cultivation of medicinal plants is such an alternative. Darjeeling Himalayan region is very rich in medicinal plant flora, but so far, it has not been able to exploit the full potential of this sector. Some Government agencies are doing some work and they have already identified certain plants for commercial cultivation and conservation, for which financial support is provided. Local NGOs are also doing some work towards cultivation of medicinal plants. This type of alternative cropping system is being proved to be a suitable livelihood strategy for this region.